Hots: Evidence from TIMSS 2011 & its implication towards stem - Jayarajah, K.; Mohd Saat, R.; Abdul Rauf, R.A. (2013)
Science, Technology, Engineering and Mathematics (STEM) education aims to prepare all students with higher order thinking skills to succeed in the 21st century. However, based on The Trends in International Mathematics and Science Study (TIMSS) in 2011, Malaysian students are still weak in higher order thinking skills (HOTS) not only in answering science questions but also in solving science problems. This research was carried out through a microanalysis of TIMSS 2011 in the science assessment. The study found out that Malaysia performed lower than the international average benchmarking in all the cognitive domains except for reasoning in Biology. In fact Singapore and Thailand out performed Malaysia in TIMSS 2011. Malaysia’s science education system requires a path of improvement which includes increasing higher order thinking skills mainly in reasoning domain. Reasoning is a crucial thinking skill in the growing interest of Science, Technology, Engineering and Mathematics (STEM) across the globe.